(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The scientific article considers the state of the energy sector of the Ukrainian economy and determines a high level of depreciation of equipment, as a result of which conclusions were drawn on the need for the speedy introduction of renewable energy, the main investor of this project is the business sector and the population of the country. An example we selected wind energy installation, for which the payback model equipment for the term of its operation. A key lever for the introduction of renewable energy is the ratio of feed-in and network tariffs, which should ensure the effectiveness of investment. In this model, the investor’s income is calculated on the basis of the network tariff for own consumption and the feed-in tariff for the energy supply of the balances from consumption to the grid. It’s proved that the development of renewable energy is important for the Ukrainian economy and business, both from the point of view of energy security, and the commissioning of new generating capacities, ensuring environmental compatibility, which, in particular, includes wind energy.